FEAR OF MISSING OUT AND COMPULSIVE BUYING IN LIVE STREAMING COMMERCE: A BIBLIOMETRIC REVIEW WITH INSIGHTS FROM ISLAMIC BUSINESS ETHICS - Zul Fahmi; Yunia Wardi; Rino; Astri Yuza sari (Ekonomi Islam, 2026)
Research aims: This study aims to systematically map the intellectual structure, research trends, and thematic evolution of Fear of Missing Out (FoMO) and compulsive buying in live streaming commerce through a PRISMA-based bibliometric review, while examining ethical implications of FoMO-driven marketing practices from the perspective of Islamic business ethics. Design/Methodology/Approach: This study employs a PRISMA-guided systematic literature review combined with bibliometric analysis of Scopus-indexed journal articles published between 2020 and 2025. Data from Google Scholar were analyzed using VOSviewer to identify dominant themes, influential studies, and research clusters through co-occurrence and network mapping. Research findings: The findings reveal convergence between FoMO, live streaming features, and social media marketing in driving compulsive consumption, while ethical implications remain underexplored. From an Islamic business ethics perspective, FoMO-driven practices conflict with principles of moderation, rationality, and consumer well-being, underscoring the need for ethically grounded strategies. Theoretical Contribution/Originality: This study advances digital marketing literature by integrating PRISMA-based bibliometric mapping with Islamic business ethics. It extends FoMO and compulsive buying theory by introducing an ethical lens that challenges performance-driven perspectives, linking emotional consumption mechanisms with principles of moderation, rational decision-making, and consumer well-being. Practitioners/Policy Implications: Practitioners and policymakers should limit FoMO-based marketing strategies and promote ethical, transparent, and consumer-protective regulations to ensure sustainable practices. Research Limitations/Implications: This study relies on Scopus-indexed bibliometric analysis, limiting contextual depth; future studies should adopt empirical and cross-cultural approaches